FECUNDITY AND BIOMASS OF Artemia franciscana FED DIFFERENT FEED TYPES - Putri Anugerah; Heru Kusdianto; Ismail Fahmy Almadi; Zulkisam Pramudia; Karina Farkha Dina (Universitas Mataram, 2026)
Artemia franciscana is an essential live food in fish and shrimp hatchery operations, whose nutritional value is significantly influenced by the feed provided during culture. Providing high-quality, cost-effective feed remains a major challenge in the mass production of A. franciscana. This study aimed to evaluate the effect of different feed types on the fecundity and biomass of Artemia franciscana. The experiment was conducted at the Nutrition and Natural Feed Laboratory, Faculty of Fisheries and Marine Sciences, Mulawarman University, over 30 days (August–September 2024). A completely randomized design (CRD) with four treatments and four replications (n = 16 experimental units) was employed. Treatments consisted of P1 (spirulina flour), P2 (soybean meal), P3 (palm kernel cake), and P4 (a mixture of spirulina flour, soybean meal, and palm kernel cake at 1:1:1 w/w ratio). Data were analyzed using one-way analysis of variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT) at a 95% confidence level. Results demonstrated that feed type had a highly significant effect (P<0.01) on the fecundity and biomass of A. franciscana. The highest fecundity was achieved in P4 (100.00 ± 4.40 nauplii/female), followed by P1 (86.00 ± 3.37 nauplii/female), P2 (71.25 ± 2.99 nauplii/female), and P3 (53.75 ± 3.50 nauplii/female). The highest final biomass was similarly recorded in P4 (1.75 ± 0.07 g/L), followed by P1 (1.49 ± 0.06 g/L), P2 (1.23 ± 0.05 g/L), and P3 (0.92 ± 0.05 g/L). All treatments differed significantly from each other based on DMRT (P<0.05). Water quality parameters remained within ranges supportive of A. franciscana survival and reproduction throughout the study. The mixed feed provided a more balanced nutrient profile, yielding the highest reproductive performance and biomass accumulation in Artemia franciscana.